Disruption of N-acyl-homoserine lactone-specific signalling and virulence in clinical pathogens by marine sponge bacteria - Gutiérrez Barranquero, José Antonio; Reen, F. Jerry; López Parages, María; McCarthy, Ronan; Dobson, Alan; O´Gara, Fergal (Wiley, 2019)
In recent years, the marine environment has been the subject of increasing attention from biotechnological and pharmaceutical industries. A combination of unique physicochemical properties and spatial niche-specific substrates, in wide-ranging and extreme habitats, underscores the potential of the marine environment to deliver on functionally novel bioactivities. One such area of ongoing research is the discovery of compounds that interfere with the cell–cell signalling process called quorum sensing (QS). Described as the next generation of antimicrobials, these compounds can target virulence and persistence of clinically relevant pathogens, independent of any growth-limiting effects. Marine sponges are a rich source of microbial diversity, with dynamic populations in a symbiotic relationship. In this study, we have harnessed the QS inhibition (QSI) potential of marine sponge microbiota and through culture-based discovery have uncovered small molecule signal mimics that neutralize virulence phenotypes in clinical pathogens. This study describes for the first time a marine sponge Psychrobacter sp. isolate B98C22 that blocks QS signalling, while also reporting dual QS/QSI activity in the Pseudoalteromonas sp. J10 and ParacoccusJM45. Isolation of novel QSI activities has significant potential for future therapeutic development, of particular relevance in the light of the pending perfect storm of antibiotic resistance meeting antibiotic drug discovery decline.
Keywords: Ecología microbiana; Esponjas marinas; Señalización bacteriana; Inhibición quorum sensing